Primary Gastrointestinal T-Cell Lymphoma and Indolent Lymphoproliferative Disorders: Practical Diagnostic and Treatment Approaches - Midori Filiz Nishimura (MDPI AG, 2021)
Primary gastrointestinal (GI) T-cell neoplasms are extremely rare heterogeneous disease entities with distinct clinicopathologic features. Given the different prognoses of various disease subtypes, clinicians and pathologists must be aware of the key characteristics of these neoplasms, despite their rarity. The two most common aggressive primary GI T-cell lymphomas are enteropathy-associated T-cell lymphoma and monomorphic epitheliotropic intestinal T-cell lymphoma. In addition, extranodal natural killer (NK)/T-cell lymphoma of the nasal type and anaplastic large cell lymphoma may also occur in the GI tract or involve it secondarily. In the revised 4th World Health Organization classification, indolent T-cell lymphoproliferative disorder of the GI tract has been incorporated as a provisional entity. In this review, we summarize up-to-date clinicopathological features of these disease entities, including the molecular characteristics of primary GI T-cell lymphomas and indolent lymphoproliferative disorders. We focus on the latest treatment approaches, which have not been summarized in existing reviews. Further, we provide a comprehensive review of available literature to address the following questions: How can pathologists discriminate subtypes with different clinical prognoses? How can primary GI neoplasms be distinguished from secondary involvement? How can these neoplasms be distinguished from non-specific inflammatory changes at an early stage?